2011
DOI: 10.1089/cyber.2010.0108
|View full text |Cite
|
Sign up to set email alerts
|

Has Cyber Technology Produced a New Group of Peer Aggressors?

Abstract: Cyber technology provides a new venue for the expression of aggression. However, whether cyber technology has produced a new group of peer aggressors or simply allowed aggressive peers new tools to victimize others is unclear. This study sampled 1,672 adolescents to assess their engagement in cyber aggression. Although "cyber," "overt," and "relational" represent distinct subtypes of aggressive behavior, our results indicate that adolescents' behaviors clustered according to their frequency-not type-of aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 29 publications
4
61
0
5
Order By: Relevance
“…Findings from this study are inline with recent research [2], [9] that has found cyber to be a separate construct from school-based victimization. Although physical and verbal items combined to form one factor, relational remained a distinct construct from cyber and direct.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Findings from this study are inline with recent research [2], [9] that has found cyber to be a separate construct from school-based victimization. Although physical and verbal items combined to form one factor, relational remained a distinct construct from cyber and direct.…”
Section: Discussionsupporting
confidence: 90%
“…These shortcomings have led to years of inconsistent findings and no universally accepted measure of victimization [2], [4], [9], [10]. This study attempts to address some of these gaps by developing a new measure of victimization and examining its construct validity in a sample of 9 th grade students.…”
Section: Purpose Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Otros investigadores, como Dempsey et al (2011), llegan a la conclusión de que Internet sí genera nuevas herramientas útiles para el acoso. Estos autores basan esta afirmación en el hecho de que los análisis factoriales que realizan indican que los tres tipos de agresiones estudiadas (directas, agresión que se produce en el entorno fuera de Internet sin provocación previa; relacionales, agresión en el entorno sin conexión con provocación previa; y acoso en el ciberespacio, agresión en el ámbito en línea) se agrupan en diferentes factores latentes, por lo que parecen ser fenómenos diferentes.…”
Section: Entorno En Líneaunclassified